Amanah sebagai Konsep Pengendalian Internal pada Pelaporan Keuangan Masjid (Studi Kasus pada Masjid Agung Oesman Al-Khair di Sukadana, Kabupaten Kayong Utara, Tahun 2022) - Wahdah, Wahdah (Undergraduate Program in Accounting, Department of Accounting, Faculty of Economics and Business, Universitas Tanjungpura, 2024)
This study aims to examine trustworthiness as a form of internal control in the implementation of ISAK 35 for mosque financial reporting. The study employs a descriptive qualitative approach using primary data obtained through interviews and secondary data in the form of the 2022 financial reports of the Oesman Al-Khair Grand Mosque. ISAK 35 is used as the analytical framework for evaluating the presentation of financial statements for a non-profit entity. Data were analyzed through data reduction, data presentation, and conclusion drawing. The results indicate that the financial management of the Oesman Al-Khair Grand Mosque has been implemented reasonably well, particularly through the authorization of each transaction by the daily treasurer, general treasurer, secretary, and general chairperson. However, the presentation of its financial statements does not yet comply with ISAK 35 because the reports only consist of records of cash receipts and disbursements. Financial information is also communicated only after Friday prayers and is limited to weekly infaq receipts. These findings show that the value of trustworthiness has supported internal control, but the mosque still needs to improve the completeness and transparency of its financial reporting in accordance with ISAK 35.